Compreensões dos professores de língua portuguesa sobre os pressupostos teórico-metodológicos das Diretrizes Curriculares do Estado do Paraná: o trabalho com os gêneros discursivos em sala de aula - Menezes, Estela Mari Tomazelli Silveira (2016)
The theme of this research is to work with the discursive genre in grades of 6 to 9 years of elementary education in public schools in the State Network, from what is proposed in the State Curriculum Guidelines (PARANÁ, 2008). Interest in the subject is based on the concern that, in working with the language does not consider the genres, we incur the risk of focusing on the language just as form and structure, revealing another conception of language that departs from that advocated by this document curriculum that guides education in the State of Paraná. From this perspective, our purpose was to answer the following research questions: a) What is the understanding of the Professor of Portuguese Language (LP) in the state schools of Cascavel, in relation to the theoretical and methodological assumptions of State Curriculum Guidelines, at work with genres in the classroom? b) How does this understanding is transpiring in the teaching of discipline referrals? c) Continuous training supplied by the State after the publication of the State Curriculum Guidelines has favored the understanding of theoretical and methodological assumptions of this document? As a general objective we propose to check on going work with the genres in groups of 6 to 9 years of elementary school in Cascavel State public network, from what is proposed in the State Curriculum Guidelines and the training, after the implementation of the document, contributing in some way for that to happen. In order that the goal was met, it was necessary to elect a theoretical framework that were in accord with what is proposed by the DCE, to explore concepts such as dialogical conception of language, speech, discursive genres, utterance and text, which are presented by Bakhtin / Volochínov (2009 [1929]) and Bakhtin (2003 [1979]; 2010 [1929]; 2010 [1975]). Resorted also to other authors who share this theory: Brait (2003, 2005, 2012); Rodrigues (2005); Faraco (2009, 2011); Acosta-Pereira (2013); Costa Hübes (2014); among others. It is, therefore, a search that is included in the Applied Linguistics, given that he turned to the study of language in the educational field. As for the methodological perspective, this research enroll in a qualitative-interpretative approach, ethnographic, case study. The subjects were 4 teachers working in the final years of elementary school in two state schools in Cascavel, and the data was generated through interviews and classroom observation. As a result, we found that teachers facing as research subjects, even though not fully understanding the theoretical and methodological basis of the document and not getting enough subsidies through FC offered by the state, teach your classes around the content discursive genre with autonomy, exploiting it in accordance with their knowledge on the subject